2017
DOI: 10.1016/j.matlet.2017.03.142
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic extrusion compression angular pressing (CECAP) as a novel severe plastic deformation method for producing bulk ultrafine grained metals

Abstract: In the current study, a novel severe plastic deformation (SPD) technique entitled cyclic extrusion channel angular pressing (CECAP) is proposed appropriate for producing ultrafine grained cylindrical material. In this new method, cyclic extrusion compression (CEC) and equal channel angular pressing (ECAP) processes are combined which solves drawbacks of both processes.Advantageous of the new process may be considered in two views of points of processing and properties. This new process increases the hydrostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…This result indicated that the combined processing route of low-pass ECAP with short-time aging can simultaneously improve both the strength and ductility of the AZ91 alloy. Figure 10c compares the UTS and elongation of the AZ91 ECAP-aged alloys with AZ91 processed by other processing approaches adopted by other studies, including ECAP [8,17,[25][26][27][28][29][30][31][32], accumulative roll bonding [9], differential speed rolling [33,34], rolling [35,36], and multidirectional forging [5]. It is obvious that there was a trade-off between the strength and ductility of the AZ91 alloy processed by conventional deformation or SPD.…”
Section: Microstructure Evolution During Processingmentioning
confidence: 98%
“…This result indicated that the combined processing route of low-pass ECAP with short-time aging can simultaneously improve both the strength and ductility of the AZ91 alloy. Figure 10c compares the UTS and elongation of the AZ91 ECAP-aged alloys with AZ91 processed by other processing approaches adopted by other studies, including ECAP [8,17,[25][26][27][28][29][30][31][32], accumulative roll bonding [9], differential speed rolling [33,34], rolling [35,36], and multidirectional forging [5]. It is obvious that there was a trade-off between the strength and ductility of the AZ91 alloy processed by conventional deformation or SPD.…”
Section: Microstructure Evolution During Processingmentioning
confidence: 98%
“…[243] Cyclic flaring and sinking (CFS) [244] Large strain extrusion machining (LSEM) [245] Cyclic extrusion compression angular pressing (CECAP) [246] 20…”
Section: Summery and Conclusionmentioning
confidence: 99%
“…Although numerous SPD processes have been introduced, not all the existing methods can be listed here owing to the continuing research in this field. However, the examples are high pressure sliding [14], high pressure tube twisting [15], friction stir processing [16], equal channel angular drawing [17], ECAP-partial back pressure [18], accumulative back extrusion [19], accumulative roll bonding [20], accumulative spin bonding [21], constrained groove pressing [22], constrained studded pressing [23], parallel tubular channel angular pressing [24], tube channel pressing [25], elliptical cross-section spiral equal-channel extrusion [26], C-shape equal channel reciprocating extrusion [27], half channel angular extrusion [28], cyclic extrusion compression [29], cyclic closed die forging [30], cyclic expansion extrusion [31], cyclic extrusion compression angular pressing [32], (variable lead) axi-symmetric forward spiral extrusion [33,34], forward shear normal extrusion [35], rotary extrusion [36], torsion extrusion (TE) [37], twist extrusion (TE) [38], simple shear extrusion [39], continuous shearing [40], continuous confined strip shearing [41], continuous frictional angular extrusion [42], repetitive corrugation straightening [43], severe torsion straining [44], and so on.…”
Section: Severe Plastic Deformation Processesmentioning
confidence: 99%